2011
DOI: 10.1007/s11694-011-9109-5
|View full text |Cite
|
Sign up to set email alerts
|

Low-fat sweet syrup cheese ball (Rosogolla) manufacturing and effect of lowering fat on quality

Abstract: Low-fat sweet syrup cheese ball (Rosogolla) was manufactured by using low-fat cow milk and implementing six different combinations viz. type of chhana and two different concentrations (40 and 508 Brix) of cooking medium. Experimental Rosogolla samples and control were analysed for physico-chemical, textural and sensory properties. A 408 Brix concentration of sugar syrup as a cooking medium gave a highly acceptable low-fat Rosogolla. Average composition of low-fat Rosogolla is, moisture-49.83%, fat-4.66%, prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…It was observed that a higher fat content resulted in a lower springiness value, which is similar to the findings reported by Kumar et al, 2003. [29] Adhesiveness of all the rasgulla samples were found as follows -NR (0.093±0.003 N-mm) > PP (0.088±0.002 Nmm) > PF (0.085±0.002 N-mm) > PMWC (0.082±0.001 Nmm) > PMW (0.081±0.002 N-mm) > PH (0.078±0.000 Nmm). In the case of adhesiveness, protein content was found as the most predominant factor.…”
Section: Texturementioning
confidence: 91%
See 2 more Smart Citations
“…It was observed that a higher fat content resulted in a lower springiness value, which is similar to the findings reported by Kumar et al, 2003. [29] Adhesiveness of all the rasgulla samples were found as follows -NR (0.093±0.003 N-mm) > PP (0.088±0.002 Nmm) > PF (0.085±0.002 N-mm) > PMWC (0.082±0.001 Nmm) > PMW (0.081±0.002 N-mm) > PH (0.078±0.000 Nmm). In the case of adhesiveness, protein content was found as the most predominant factor.…”
Section: Texturementioning
confidence: 91%
“…There are several studies on the texture of rasgulla with respect to different characteristics and other conditions as well. [29][30][31][32][33] Hardness values (expressed in Newton (N)) of all the rasgulla samples were observed in the following order -NR (5.26±0.29 N) <PP (5.31±0.19 N) <PF (5.38±0.27 N) <PH (5.41±0.23 N) <PMW (5.49±0.37 N) <PMWC (5.55±0.49 N). From all these values, it can be seen that as the fat content of rasgulla samples (Table 1) is decreased as the hardness value is increased.…”
Section: Texturementioning
confidence: 99%
See 1 more Smart Citation
“…Rosogolla is most popular sweetmeat which is highly acceptable to the people for its characteristics texture and a pleasant sweetness (Desai et al, 1993). It has high nutritional value because of its digestibility and high protein, fat, mineral content, particularly Ca and P, as well as fat-soluble vitamins A and D. (Kumar and Prasad, 2010;Prajapati et al, 2011). Rosogolla has 186 calories per 100g, with 153, 16, and 17 calories coming from carbohydrate, protein, and fat, respectively (Gurveer and Goswami, 2017).…”
Section: Introductionmentioning
confidence: 99%